2014
DOI: 10.1104/pp.114.249052
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation in Sensitivity to a Loss of Chloroplast Translation in Arabidopsis    

Abstract: Mutations that eliminate chloroplast translation in Arabidopsis (Arabidopsis thaliana) result in embryo lethality. The stage of embryo arrest, however, can be influenced by genetic background. To identify genes responsible for improved growth in the absence of chloroplast translation, we examined seedling responses of different Arabidopsis accessions on spectinomycin, an inhibitor of chloroplast translation, and crossed the most tolerant accessions with embryo-defective mutants disrupted in chloroplast ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 103 publications
(158 reference statements)
5
72
0
Order By: Relevance
“…Duplication of the homomeric ACCase and retargeting to the plastids has occurred repeatedly and independently during angiosperm evolution ( Figure S3). The observed duplication in our data set preceded the divergence between Agrostemma and Silene, but it was independent from similar duplications in grasses (Konishi and Sasaki 1994) and the Brassicaceae (Schulte et al 1997;Babiychuk et al 2011;Parker et al 2014).…”
Section: Clp and Accase Gene Content In The Tribe Sileneaementioning
confidence: 93%
See 1 more Smart Citation
“…Duplication of the homomeric ACCase and retargeting to the plastids has occurred repeatedly and independently during angiosperm evolution ( Figure S3). The observed duplication in our data set preceded the divergence between Agrostemma and Silene, but it was independent from similar duplications in grasses (Konishi and Sasaki 1994) and the Brassicaceae (Schulte et al 1997;Babiychuk et al 2011;Parker et al 2014).…”
Section: Clp and Accase Gene Content In The Tribe Sileneaementioning
confidence: 93%
“…Together, these enzymes convert acetyl-CoA to malonyl-CoA within the plastid, which is the first step in the fatty acid biosynthesis pathway (White et al 2005). In some lineages, the homomeric ACCase has undergone a duplication, and one copy is targeted to the plastid while the other remains in the cytosol (Konishi and Sasaki 1994;Schulte et al 1997;Babiychuk et al 2011;Parker et al 2014).…”
mentioning
confidence: 99%
“…Most grasses lack the heteromeric enzyme altogether and instead utilize a plastid-localized homomeric enzyme produced from a duplicated nuclear gene (Konishi and Sasaki, 1994;Chalupska et al, 2008). Previously, we showed that natural variation in the response of Arabidopsis embryos and seedlings to a loss of chloroplast translation is mediated by ACC2, and that tolerant accessions likely contain functional ACC2 along with an unlinked enhancer of ACC2 function and modifiers that extend the growth response (Parker et al, 2014). Overall, the focus of that initial study was on identifying factors that improved survival in the absence of chloroplast translation.…”
mentioning
confidence: 99%
“…Weak alleles exhibit altered cuticular wax composition, cold sensitivity, and glossy inflorescence stems (Lü et al, 2011;Amid et al, 2012). Loss of the heteromeric, chloroplast-localized enzyme, by contrast, results in early embryo lethality (Li et al, 2011), with the stage of arrest dependent on genetic background (Parker et al, 2014). In some members of the Brassicaceae, including Arabidopsis, a tandem ACC1 gene duplication enables the production of a chloroplasttargeted homomeric enzyme (ACC2) that can partially suppress the early lethality associated with a loss of chloroplast translation and the absence of heteromeric ACCase (Yanai et al, 1995;Babiychuk et al, 2011;Bryant et al, 2011).…”
mentioning
confidence: 99%
“…As illustrated in Figure 1, in addition to the major photosynthetic-type TIC (i.e., the green TIC containing Ycf1 that predominantly functions in green tissues), there appears to be an alternative nonphotosynthetic-type minor TIC import system for a certain subset of proteins. This system includes the Tic20 paralog Tic20-IV in Arabidopsis but lacks Tic56, Tic100, and Tic214 (Hirabayashi et al, 2011;Kikuchi et al, 2013;Parker et al, 2014;Nakai, 2015). Experimental data shown in recent work by Kö hler et al (2015) provide support for this model of more than one TIC complex.…”
Section: How Can We Explain the Evolutionary History Of Ycf1 Includimentioning
confidence: 73%